(untitled) (Management Studies and Business Journal (PRODUCTIVITY), 2025)
Kaleke Village in Sigi Regency, Central Sulawesi, is developing the tourism potential of Bionga Baths through cooperation between BUMDes, Pokdarwis, and the local community. This study aims to analyze the extent to which this cooperation supports tourism sustainability and community welfare. The research uses a qualitative method with techniques such as observation, interviews, and documentation. Data analysis is carried out through data reduction, data presentation, and data verification. The validity of the data is checked using source triangulation, technique triangulation, and time triangulation. The results show that there are four economic cooperation programs: facility improvement, tourism package provision, tourism promotion, and financing, management, and maintenance of tourism. This cooperation is complementary and focuses on community empowerment, cultural preservation, and directly increasing community income. The challenges in this cooperation include funding dependence, limited resources, lack of facilities, land acquisition issues, and suboptimal management. The cooperation reflects Islamic economic principles through justice, mutual assistance, and sustainability. The implications of this study highlight the importance of local policy, training, and funding diversification.